Safety of intravenous iron isomaltoside for iron deficiency and iron deficiency anemia in pregnancy - Wesström, Jan (Arch Gynecol Obstet, 2020)
PURPOSE: To evaluate the efficacy and safety for mother and child of using intravenous iron isomaltoside (IV-IIM) during pregnancy. METHODS: Using an appointment register, we retrospectively identified all pregnant women who received a single dose of 1000 or 1500 mg IV-IIM in the maternity ward of Falu Hospital and subsequently gave birth between August 6, 2013 and July 31, 2018. Women who received IV-IIM (case group) were individually matched with pregnant women who did not receive IV-IIM (control group) by delivery date, maternal age (± 2 years), and parity. Adverse drug reactions (ADRs), demographic characteristics, hemoglobin and s-ferritin counts, pregnancy and delivery complications, and infant data (APGAR score, pH at umbilical artery, birthweight, birth length, intrauterine growth restriction and neonatal ward admission). Data were obtained from electronic patient charts. SPSS was used for descriptive statistics. RESULTS: During the 5-year period, 213 women each received a single administration of IV-IIM. Ten (4.7%) ADRs occurred during IV-IIM administration. All ADRs were mild hypersensitivity reactions, abated spontaneously within a few minutes, and did not recur on rechallenge. No association between IIM dose and ADR frequency was noted. Maternal and fetal outcomes, including hemoglobin counts at delivery and postpartum, were similar in the case and control groups. CONCLUSION: These results support the convenience, safety, and efficacy of a single high-dose (up to 1500 mg) infusion of IV-IIM for iron deficiency or iron deficiency anemia during pregnancy.